The Development Of Collision Module Based On Process Image For Physics Learning In Senior High School - Fajar Lailatul Mi’rojiyah; Sutarto Sutarto; I Ketut Mahardika; Indrawati Indrawati; Jekti Prihatin (Pancaran Pendidikan, 2017)
This action research explored the development of instructional material in module form based on process image which valid, practice, and effective at physics learning in senior high school. Physics contained the concepts with the fundamental categorising something into presenting on verbal so the physics concepts are usually abstract so that mental image needed. The development of this module is one of instructional material which can help the student thinking systematic about the physics concepts so that it can learn by students independently. The module must be describing the basic competencies and it will be achieved by students and served with a good language, interesting, and completed by illustration clearly. Process Image interpreted by a series of images (objects, events, phenomenon), which every image of that series always look a different combination overall describing phase stages comprehensive.The development of module in this research is using Thiagarajan design research and development 4D (Define, Design, Develop and Disseminate) and it still at the phase Develops which the result through expert validation and action research that is a plan, action, observe, and reflection during the research. Finally, the collision module based on process image can be used in physics learning.